Source Rock Quality and 1D Maturity Model in Pendalian Sub-basin, Central Sumatra Basin - Putri Dwi Afifah; Hendra Amijaya; Sarju Winardi; Widi Atmoko (Geological Engineering Department Universitas Gadjah Mada, 2023)
Pematang Formation is well known as the main source rock in the Central Sumatra Basin (Mazied et al., 2008). The formation which acts as source rock has been studied thoroughly in the central and eastern parts of the basin, but research regarding source rock in the western part of the basin, which is the study area, is very limited. This paper aims to define the quality of source rock from a geochemical view through the determination of organic content quantity based on the Total Organic Carbon (TOC) data, determining the type of kerogen, and thermal maturity of the source rock according to the values of Tmax and Vitrinite Reflectance (%Ro). Burial history and thermal maturity models (1D basin modeling) were also constructed to understand the timing of hydrocarbon generation. The results show that Pematang Formation among Sihapas and Telisa Formation has good organic content with TOC ranging from 0.2 to 42.48 wt%, and the maturity parameters indicate that the Pematang Formation has reached the mature stage. Both formations are dominated by Type II kerogen. 1D modeling of the SHT-1 Well indicates that the Pematang Formation is currently in the oil maturity window starting from early oil to main oil at 20.61 Ma, but the model of the SMB-1 Well has not reached the oil maturity window. Tectonic activity is estimated to have a significant effect on this difference when the uplift activity of Bukit Barisan in the Middle Miocene increased the maturity in the northwest, but the inversion that occurred in the Late Miocene resulted in uplift and erosion of young sediments, thus lowering the temperature in some area.